Reduction of deoxynivalenol (DON) contamination by improved fungicide use in wheat. Part 2. Farm scale tests with different nozzle types and updating the integrated approach - Mesterházy Ákos (EUROPEAN JOURNAL OF PLANT PATHOLOGY, 2018)
Fungicidal control of Fusarium head blight (FHB) of wheat with fungicides generally has poor efficacy (0–40%). However, small plot trials prove that a 70– 90% reduction in toxin contamination is possible. We compared two variants of side-spraying nozzles with the Turbo FloodJet. The new nozzle combination (QJ 90, TT F, XR B) reduced visual FHB scores by 50% as compared to the standard TeeJet XR nozzles. The fungicide choice is decisive, the best product reduced DON by 81%, the least effective only by 31%. Greater genetic resistance is also decisive, the most resistant cultivar showed a 73% reduction in DON across all treatments. The combined effect of the fungicide + cultivar was 98.5% between the UTC and best fungicide/variety combination (GK Fény/PT) across three years. The new combined nozzle was more effective at the better fungicides containing prothioconazole, metconazole and tebuconazole, at the less effective fungicides its effect was only average. Correlations between small plot (Part 1) and farm tests were r = 0.96 (P = 0.001) for FHB, r = 0.91 (P = 0–001) for FDK, and r = 0.75 (P = 0.02) for DON indicating that small plot results forecast field usefulness and reduction in field control was close to the small plot results for all traits. The heart of integrated plant management (IPM) is the combination of variety resistance, the effective fungicide and the side-spraying technology with appropriate nozzle choice. Resistance governs fungicide reduction, nozzle influence, effect of previous crop and tillage. Susceptible cultivars should be withdrawn from production, but cultivars such as GK Fény treated with preventive fungicides at the flowering phase can be grown without any serious food safety risk. With a careful field-specific IPM combination, the reduction can be doubled without significant additional costs.